Complete Application Of Profiled Steel Sheeting Dry Board System As School Classroom Modules - Awang, Hanizam; Nordin, Norhaiza; Wan Badaruzzaman, Wan Hamidon (2008)

(untitled)
This paper describes the application of Profiled Steel Sheet Dry Board (PSSDB) system as innovative lightweight composite school classroom modules.